The Influence of Work Motivation and Work Discipline on Employee Performance at Delima Asih Sisma Medika Hospital in Karawang Regency - Abdulah; Prista Tarigan; Noor Sembiring (Journal of Accounting and Finance Management, 2021)
Work motivation and work discipline is one factor thataffect employee performance, the purpose of this study was to determine the effect of work motivation and work discipline on employee performance at Delima Asih Sisma Medika Hospital in Karawang Regency. Data collection techniques were through questionnaires using a Likert scale, questionnaires were given to 75 respondents, namely hospital employees , the number of respondents based on the slovin formula with an alpha of 10%. Data analysis techniques with instrument test, classical assumption test, multiple linear regression test and T test and F test. The results of this study indicate that work motivation and work discipline have a positive and significant effect either partially or simultaneously on employee performance at Delima Asih Sisma Hospital Medika in Karawang Regency.